The ripple-curry amplifier in photonic applications - Gilewski, Marian (Photonics Letters of Poland, 2022)
This paper discusses the new design of a amplifier for the miniature MEMS-type spectrometer. The application problem of the new amplifier was the correct conditioning of the sensor’s photoelectric pulses. The processed signal was a sequence of pulses that had variable both frequency and amplitude value. Thus, such a broadband amplifier should have the functionality of automatic gain control. This paper describes the concept of the new circuit, develops its detailed application, and then performs validation tests. Measurement results of the new circuit are discussed in the final section of the paper. Full Text: PDF References C. Ortolani, Flow Cytometry Today. Detectors and Electronics, (Springer 2022). pp. 97-119, CrossRef D. Maes, L. Reis, S. Poelman, E. Vissers, V. Avramovic, M. Zaknoune, G. Roelkens, S. Lemey, E. Peytavit, B. Kuyken, "High-Speed Photodiodes on Silicon Nitride with a Bandwidth beyond 100 GHz", Conference on Lasers and Electro-Optics, Optica Publishing Group, (2022). CrossRef R. Das, Y. Xie, A.P. Knights, "All-Silicon Low Noise Photonic Frontend For LIDAR Applications", 2022 IEEE Photonics Conference (IPC), IEEE Xplore (2022). CrossRef FEMTO Messtechnik GmbH, Variable Gain Photoreceiver - Fast Optical Power Meter Series OE-200, DirectLink M. Nehir, C. Frank, S. Aßmann, E.P. Achterberg, "Improving Optical Measurements: Non-Linearity Compensation of Compact Charge-Coupled Device (CCD) Spectrometers", Sensors 19(12), 2833 (2019). CrossRef F. Thomas,; R. Petzold, C. Becker, U. Werban, "Application of Low-Cost MEMS Spectrometers for Forest Topsoil Properties Prediction", Sensors 21(11), 3927 (2021). CrossRef M. Muhiyudin, D. Hutson, D. Gibson, E. Waddell, S. Song, S. Ahmadzadeh, "Miniaturised Infrared Spectrophotometer for Low Power Consumption Multi-Gas Sensing", Sensors 20(14), 3843 (2020). CrossRef S. Maruyama, T Hizawa, K. Takahashi, K. Sawada, "Optical-Interferometry-Based CMOS-MEMS Sensor Transduced by Stress-Induced Nanomechanical Deflection", Sensors 18(1), 138 (2018). CrossRef S. Merlo, P. Poma, E. Crisà, D. Faralli, M. Soldo, "Testing of Piezo-Actuated Glass Micro-Membranes by Optical Low-Coherence Reflectometry", Sensors 17(3), 8 (2017). CrossRef M.S. Wei, F. Xing, B. Li, Z. You, "Investigation of Digital Sun Sensor Technology with an N-Shaped Slit Mask", Sensors 11(10), 9764 (2011). CrossRef Z. Yang, T. Albrow-Owen, W. Cai, T. Hasan, "Miniaturization of optical spectrometers", Science 371, 6528 (2021). CrossRef Hamamatsu Photonics K.K. Fingertip size, ultra-compact spectrometer head integrating MEMS and image sensor technologies. DirectLink Microchip Technology Inc, MCP6291/1R/2/3/4/5 1.0 mA 10 MHz Rail-to-Rail Op Amp, CrossRef Microchip Technology Inc. MCP6021/1R/2/3/4 Rail-to-Rail Input/Output 10 MHz Op Amps, CrossRef